Delayed Displacement of a Subtle Sacral Insufficiency Fracture Unmasking Lumbopelvic Instability: A Case Report. Issue 1 (January 2021) - Campbell, Sean T.; Firoozabadi, Reza
Abstract : Case: There is limited literature reporting on sacral insufficiency fractures as a cause of lumbopelvic instability. We describe the presentation, treatment, and clinical outcome with a 2-year follow-up of a woman who sustained a low-energy spinopelvic dissociation diagnosed with magnetic resonance imaging. There was significant delayed displacement, and the patient was treated surgically with percutaneous iliosacral and trans-sacral screws. Conclusion: U-type sacral insufficiency fractures may be subtle on advanced imaging and must be followed closely if nonoperative treatment is chosen. These patients may require surgical intervention. Iliosacral screws and lumbopelvic fixation are treatment options, each with advantages and disadvantages.